Choosing Wisely in Headache Medicine: The American Headache Society's List of Five Things Physicians and Patients Should Question. Issue 10 (29th October 2013) - Loder, Elizabeth; Weizenbaum, Emma; Frishberg, Benjamin; Silberstein, Stephen; ,
<x xml:space="preserve">Abstract</x> In an effort to draw attention to tests and procedures associated with low‐value care in headache medicine, the American Headache Society (AHS) joined the Choosing Wisely initiative of the American Board of Internal Medicine Foundation. The AHS president appointed an ad hoc "Choosing Wisely" task force of the AHS. The committee surveyed AHS members to develop a candidate list of items for the AHS "Top 5" list of low‐value care in headache medicine. Through a process of literature review and consensus, the final list of five items was chosen. Draft recommendations went through several rounds of revision and a process of outside review. The AHS Board of Directors approved the final list of "Five Things." The five recommendations approved by the AHS Board of Directors are: (1) don't perform neuroimaging studies in patients with stable headaches that meet criteria for migraine; (2) don't perform computed tomography imaging for headache when magnetic resonance imaging is available, except in emergency settings; (3) don't recommend surgical deactivation of migraine trigger points outside of a clinical trial; (4) don't prescribe opioid‐ or butalbital‐containing medications as a first‐line treatment for recurrent headache disorders; and (5) don't recommend prolonged or frequent use of over‐the‐counter pain medications for headache. We recommend that headache medicine specialists and other physicians who evaluate and treat headache disorders should use this list when discussing care with patients.